Religious Conflict and Islamic Strategies of Peacebuilding in Indonesia - Suprianto, Bibi (ADDIN, 2022)
Religious conflict is not only a matter of religion, but also a matter of human life who wants peace in life. By understanding the Islamic strategy in building peace in Indonesia, we can find conflict resolution that must be developed in life. This study argues that conflict and Islam’s strategy in building peace is a study of conflict resolution in overcoming violence and truth claims in religion. Thus, this study formulates the question of how religious conflict and Islamic strategies of peace building in Indonesia are? This study uses the library research to find sources of conflict and Islamic strategies in building peace in Indonesia. The results of this study indicate that conflict and Islamic strategies in building peace provide an overview: (1) the conflict has become a public debate about truth claims and religious violence; (2) religious culture and moderation are the strategy of Islam in building peace in Indonesia. The findings of this study indicate that conflict and Islamic strategies in building peace as conflict resolution exist in Indonesia.